A Note on Depreciation, Replacement, and Growth - Schiff, Eric (The Review of Economics and Statistics, 1954)
RECENT contributions by Professors Evsey D. Domar I and Robert Eisner2 have analyzed the conditions under which current depreciation allowances equal, exceed, or fall short of current replacement requirements. The (substantially identical) findings of both authors may be briefly summarized as follows: In a seasoned plant,3 the ratio between replacement needs and depreciation charges depends primarily on the direction, as well as the rate, of the change in (a) gross plant size and (b) the general price level. If prices are stable, straight-line depreciation charges based on original cost and spread evenly over the true service life equal current replacement in a stable plant and exceed it in a growing plant. Under price inflation they keep below replacement requirements in a stable plant, whereas in a growing plant this may or may not be so, depending on the growth rate on one hand and the rate of inflation on the other. On the basis of the formula by which both Domar and Eisner have attempted to describe the algebraic relationship among depreciation, replacement, and growth, it would appear that, if we have stable prices, a constant rate of growth of about the size that has characterized the American economy for a long time, and an average service life of capital assets roughly in accordance with American reality, depreciation charges computed in the manner indicated must exceed replacement requirements by a considerable margin. This would mean that these allowances, to the extent they are earned and saved, can finance a sizable portion of the expansion. A corollary result would be that, under the stated conditions of growth and average asset life, it takes a heavy inflation to wipe out the excess of depreciation charges over replacement needs, and a very heavy one to turn the excess into a deficit.